Planning and documenting reinforcement system test programs - Thompson, A.; Villaescusa, Ernesto; Windsor, C. (2013)
Laboratory axial tension and field pull-out tests have for many years been used to measure and evaluate the performance of reinforcement systems used to stabilise soil or rock masses. The reinforcement systems consist of varying configurations. Some test programs are poorly planned and do not provide as much useful information as otherwise could be obtained. In other cases, the results of the test programs are poorly documented so that other interested parties cannot use the results or adapt them for different circumstances. In fact, the writers' own experiences have been to return to laboratory and field notes only to find information missing from formal reports prepared some years in the past. Examples are given of the types of deficiencies of reported laboratory and field test programs and how these can be avoided by better understanding of the mechanisms of reinforcement systems. © 2013 Taylor & Francis Group.